Equity in global conservation policy varies in clarity and comprehensiveness - Hampton-Smith, Melissa; Gurney, Georgina Grace; Morrison, Tiffany Hope; Cinner, Joshua Eli (One earth (Cambridge, Mass.), 2024)
Equity is increasingly emphasized in global conservation policy because equitable practice is recognized as an ethical imperative and instrumental to conservation success. Equitable conservation involves recognition of diverse actors and their rights, inclusive decision making, and fair distribution of impacts. However, understanding of how equity is conceptualized in policy is lacking. Given the important role of policy in shaping practice, we examine how equity is articulated in seven key conservation policies. Using content analysis, we assess policies with respect to equity dimensions (recognition, procedure, and distribution), content (what the issue is about), subjects (who is considered), and criteria (elements of each dimension). We find that equity text is vague, omits essential equity criteria, and prioritizes distributional concerns over procedural and recognitional equity. The limited clarity and comprehensiveness of equity directives may hinder efforts to foster equity in practice. We suggest that clear, theoretically grounded, yet flexible equity directives are crucial to equitable on-ground conservation. [Display omitted] •How equity is conceptualized in global conservation policy shapes implementation•We assessed how equity was conceptualized in seven key global conservation policies•Treatment of equity in policies lacks clarity and varies in comprehensiveness•Policies focus on distributional equity over recognitional or procedural equity Equity is increasingly emphasized in global conservation policies, as it is seen as both an ethical imperative and crucial for conservation success. Equitable conservation recognizes diverse actors and their rights, encourages inclusive decision-making, and ensures fair distribution of costs and benefits. Understanding how equity is framed in conservation policy is limited but essential, as it shapes conservation practices and the real-world application of equity. We analyzed seven key global conservation policies, examining equity through four aspects: dimensions (recognition, procedure, distribution), content (the equity issue), subjects (who is included), and criteria (elements of each dimension). Our findings indicate that equity directives are vague, often overlook key criteria, and prioritize material resource distribution over recognizing diverse groups or fair decision-making. This resource-centric approach fails to address systemic injustices. Thus, the lack of clarity in equity directives could impede effective equitable conservation practices. Global conservation policies increasingly emphasize equity, but unclear definitions may undermine equitable conservation in practice. Our review of seven key global conservation policies reveals that, while equity is a focus, these policies often lack clarity and vary in how comprehensively they address equity. Key policies mainly concentrate on resource distribution rather than recognition of socio-cultural diversity and equitable decision-making. For more effective and equitable conservation efforts, clearer and more comprehensive treatment of equity in policies is crucial.